The Influence of the Inquiry Training Model on the Physics Learning Outcomes - Sanjaya, Felisia; Pertiwi; Hasan, Nurhikmah; Reza, Azinal; Fatmawati, Titin (UIN Alauddin Makassar, 2024)
This research aims to determine the effect of the inquiry training learning model on the physics learning outcomes of class X students at SMA Makassar Raya. The type of research used was pre-experiment with a One Group Pretest-Posttest Design. The sampling technique was simple random sampling so that the sample in this research was 20 students of class X MIPA 1. The research instruments used were lesson plans (RPP) and learning outcomes tests given before and after implementing the inquiry training learning model. Based on the results of the paired sample t-test, a significance value <0.05 was obtained, meaning that there was a difference in pretest and posttest learning outcomes. So it can be concluded that the inquiry training learning model influences students' physics learning outcomes of class X MIPA 1 SMA Makassar Raya.